Comparison of the Behavioral Changes in Pain Patterns in Brucellosis Patients under Oral Gabapentin and Naproxen Treatment: A Randomized Clinical Trial - Revjam 1, Farnaz; Nezakati 2, Ehsan; Zolfaghari 3, Pouneh; Mousapour 1, Mehrshad; Sohrabi 4*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2019)
Background: Brucellosis is a common disease between humans and animals which can cause various types of organ involvement. Of the most common and important disorders, it is a skeletal disorder that causes severe pain. The aim of this study was done to compare the behavioral changes in pain patterns in brucellosis patients under oral gabapentin and naproxen treatment. Methods: This study was a paralleled randomized controlled clinical trial on 86 patients with brucellosis disease. All 15-65-year-old patients with diagnosed brucellosis and no history of other systemic diseases were included. Patients with a history of using corticosteroids were excluded. After receiving their informed consent, the eligible patients were randomly divided into two equal groups of intervention (gabapentin) and control group (naproxen) using a block randomization method. Then, the pain severity was assessed using visual analog scale (VAS) before, as well as 4, 7, and 10 days postintervention. In this study, the patients, data collector (pain intensity assessment), and analyzer were blinded. The data were analyzed using repeated measure ANOVA. Significance level was set at 0.05. Results: Among the participants, 56 patients (65.1%) were male and the mean age of the patients was 46.85 ± 19.15 years, which was not significantly different between the two groups. In the case of painful and involved joints, sacroiliac joint with 34 cases (39.5%) was the most commonly involved joint in both groups. There was a significant difference between the two groups regarding the mean pain intensity on the fourth day (Pvalue = 0.021) and seventh day (Pvalue = 0.001), while there was no difference at other times.Conclusions: The results of this study revealed that gabapentin significantly and rapidly decreased skeletal pain in brucellosis patients. Therefore, it can be used as an appropriate drug for the control of bone and joint pain in brucellosis patients, though at least it should be used for a few day period.Keywords: Brucellosis, Gabapentin, Naproxen, Skeletal pain.